2011
DOI: 10.1038/emboj.2011.14
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsispeptide kiss of death is an inducer of programmed cell death

Abstract: Programmed cell death (PCD) has a key role in defence and development of all multicellular organisms. In plants, there is a large gap in our knowledge of the molecular machinery involved at the various stages of PCD, especially the early steps. Here, we identify kiss of death (KOD) encoding a 25-amino-acid peptide that activates a PCD pathway in Arabidopsis thaliana. Two mutant alleles of KOD exhibited a reduced PCD of the suspensor, a single file of cells that support embryo development, and a reduced PCD of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 47 publications
2
60
0
Order By: Relevance
“…To protect cell function, plants have evolved a complex metabolic adjustment process known as the heat shock response (HSR; Kotak et al, 2007;Mittler at al., 2012). Alternatively, programmed cell death is activated in specific cells, resulting in leaf shedding or abortion of reproductive organs (Qu et al, 2009;Blanvillain et al, 2011). Whereas research in forest trees remains scarce, the ubiquitous and conserved HSR has been thoroughly studied in herbaceous plants (Larkindale and Vierling, 2008;Hu et al, 2009;Finka et al, 2011;Mittler et al, 2012).…”
mentioning
confidence: 99%
“…To protect cell function, plants have evolved a complex metabolic adjustment process known as the heat shock response (HSR; Kotak et al, 2007;Mittler at al., 2012). Alternatively, programmed cell death is activated in specific cells, resulting in leaf shedding or abortion of reproductive organs (Qu et al, 2009;Blanvillain et al, 2011). Whereas research in forest trees remains scarce, the ubiquitous and conserved HSR has been thoroughly studied in herbaceous plants (Larkindale and Vierling, 2008;Hu et al, 2009;Finka et al, 2011;Mittler et al, 2012).…”
mentioning
confidence: 99%
“…Cell death markers show ZOU-dependent expression in the developing endosperm during seed development Cell death in the developing Arabidopsis seed is not restricted to the endosperm, and is also known to occur in the developing seed coat (Andeme Ondzighi et al, 2008;Nakaune et al, 2005) and the embryonic suspensor (Blanvillain et al, 2011). To identify cell death markers with relative specificity for the endosperm, we therefore interrogated available in silico resources and the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo translational GFP fusions showed that the initiation codon of KOD can be recognized for translation in planta, though it remains unclear how the KOD peptide is translated, similar as for PLS (Figure 4). Nevertheless, NMR studies on synthetic KOD peptide pointed out that it adopts an a-helix (from Pro-9 to Arg-21), whereas the N-terminal region is disordered (Blanvillain et al, 2011).…”
Section: Peptides Encoded By Sorfs In Primary Transcripts Of Mirnasmentioning
confidence: 99%
“…KOD is encoded by the longest and last ORF in a short KOD-transcript containing three sORFs in sense. Experiments using knockout mutants, carrying a T-DNA insertion and a point mutation (Pro-9 to Ser), respectively, and transient assays in onion (Allium cepa) using mutated and truncated variants of KOD indicate that KOD functions as a peptide rather than as RNA (Blanvillain et al, 2011). In vivo translational GFP fusions showed that the initiation codon of KOD can be recognized for translation in planta, though it remains unclear how the KOD peptide is translated, similar as for PLS (Figure 4).…”
Section: Peptides Encoded By Sorfs In Primary Transcripts Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation